The Influence of Work Stress and Discipline on Work Performance of Emplyee at PT. Surya Menara Pratama Jakarta Selatan - Rahmi Hermawati; Sri Handayani (PINISI Discretion Review, 2020)
The final measure of success of an HR Department is work performance. The purpose of this study was to determine how much influence work stress has on work performance of empolyee at PT Surya Menara Pratama, South Jakarta, to find out how much influence discipline has on employee performance at PT Surya Menara Pratama, South Jakarta, and to determine the Effect of Work Stress and Discipline Towards Employee Job Performance at PT Surya Menara Pratama, South Jakarta. The research method used is a quantitative method with descriptive explanation. The population in this study were employees of PT Surya Menara Pratama South Jakarta with a sample of 60 and the sampling technique used was the Simple Random Sampling technique. Furthermore, the analysis method used in this study is multiple linear regression analysis consisting of descriptive analysis of the questionnaire, validity test, reliability test, classic assumption test, coefficient of determination test correlation coefficient test, simple regression test, multiple linear regression test, t test (test partial), f test (simultaneous test). The results of simple linear regression analysis show that work stress has a significant effect on work performance with a tcount of 3.902, a significance value of 0.000, a regression coefficient of 0.436 and a regression equation Y = 24.167 + 0.436X1. The results of simple linear regression analysis show that work discipline has a significant effect on work performance with a tcount of 3,500, a significance value of 0.001, a regression coefficient of 0.400 and a regression equation Y = 25.804 + 0.400X2. The results of multiple linear regression analysis show that work stress and work discipline simultaneously have a significant effect on work performance with a Fcount of 10.923, a significance value of 0.000, a coefficient of determination of 0.252 and a regression equation Y = 17.293 + 0.332X1 + 0.273X2.